Predictors of early death in female patients with breast cancer in the UK: a cohort study. Issue 2 (28th November 2011) - Stapelkamp, Ceilidh; Holmberg, Lars; Tataru, Daniela; Møller, Henrik; Robinson, David
Abstract : Objective: To identify factors predicting early death in women with breast cancer. Design: Cohort study. Setting: 29 trusts across seven cancer networks in the North Thames area. Participants: 15 037 women with primary breast cancer diagnosed between January 1996 and December 2005. Methods: Logistic regression analyses to determine predictors of early death and factors associated with lack of surgical treatment. Main exposures: Age at diagnosis, mode of presentation, ethnicity, disease severity, comorbidities, treatment and period of diagnosis in relation to the Cancer Plan (the NHS's strategy in 2000 for investment in and reform of cancer services). Main outcome measures: Death from any cause within 1 year of diagnosis, and receipt of surgical treatment. Results: By 31 December 2006, 4765 women had died, 980 in the year after diagnosis. Older age and disease severity independently predicted early death. Women over 80 were more likely to die early than women under 50 (OR 8.05, 95% CI 5.96 to 10.88). Presence of distant metastases on diagnosis increased the odds of early death more than eightfold (OR 8.41, 95% CI 6.49 to 10.89). Two or more recorded comorbidities were associated with a nearly fourfold increase. There was a significant decrease in odds associated with surgery (OR 0.29, 95% CI 0.24 to 0.35). Independently of disease severity and comorbidities, women over 70 were less likely than those under 50 to be treated surgically and this was even more pronounced in those aged over 80 (OR 0.09, 95% CI 0.07 to 0.10). Other factors independently associated with a reduced likelihood of surgery included a non-screening presentation, non-white ethnicity and additional comorbidities. Conclusions: These findings may partially explain the survival discrepancies between the UK and other European countries in female patients with breast cancer. The study identifies a group of women with a particularly poor prognosis for whom interventions aiming at early detection may be targeted.